Dynamic mapping of the human visual cortex by high-speed magnetic resonance imaging. - Blamire, A M (1992)
We report the use of high-speed magnetic resonance imaging to follow the changes in image intensity in the human visual cortex during stimulation by a flashing checkerboard stimulus. Measurements were made in a 2.1-T, 1-m-diameter magnet, part of a Bruker Biospec spectrometer that we had programmed to do echo-planar imaging. A 15-cm-diameter surface coil was used to transmit and receive signals. Images were acquired during periods of stimulation from 2 s to 180 s. Images were acquired in 65.5 ms in a 10-mm slice with in-plane voxel size of 6 x 3 mm. Repetition time (TR) was generally 2 s, although for the long flashing periods, TR = 8 s was used. Voxels were located onto an inversion recovery image taken with 2 x 2 mm in-plane resolution. Image intensity increased after onset of the stimulus. The mean change in signal relative to the prestimulation level (delta S/S) was 9.7% (SD = 2.8%, n = 20) with an echo time of 70 ms. Irrespective of the period of stimulation, the increase in magnetic resonance signal intensity was delayed relative to the stimulus. The mean delay measured from the start of stimulation for each protocol was as follows: 2-s stimulation, delay = 3.5 s (SD = 0.5 s, n = 10) (the delay exceeds stimulus duration); 20- to 24-s stimulation, delay = 5 s (SD = 2 s, n = 20).